От всего сердца: роман / Д. Гудмэн ; пер. с англ. Р. Н. Волошина - Гудмэн Джо (Очарование, 2000)
Экземпляры: ф.22 (2014) / Инвентарный номер: 56195 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Г 93 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44